Kebijakan Perencanaan Pajak Melalui Instrumen Natura dan Zakat Untuk Meminimalkan Pajak Penghasilan Badan Pada PT Milenium Kreasi - Albas Tomi; Yanti Budiasih (Indonesian Journal of Economics Application (IJEA), 2020)
The purpose is to assess and analyze the accuracy of tax planning at PT. Millennium Kreasi. To studty and analyze the amount of tax planning carried out by PT. Millennium Kreasi. To find out the amount of tax savings obtained by PT. Millennium Kreasi by doing tax planning. The data used in this study are secondary data from PT. Millennium Kreasi. This study uses a descriptive qualitative method with data collection techniques in literature and Fields studies. Based on the results of this study The application of tax planning at PT. Millennium Kreasi is considered very appropriate by researchers, this is based on that after the tax planning was carried out, PT. Millennium Kreasi can minimize the tax burden owed to PT. Millennium Kreasi. In this study, the researcher can minimize PT. Millennium payable income tax expense of IDR 49,581,535. Ie, with the details of the application of zakat payments of IDR 32,249,030, and the application of giving in kind of IDR 17,332,505. In this calculation, the Corporate Tax that must be paid by PT. Millenium Kreasi before tax planning is IDR 482,273,115, and the Corporate Income Tax that must be paid by PT Millennium Kreasi after tax planning is IDR 432,691,580.